Baseline profile and results of atrial fibrillation ablation in patients with arrhythmia-induced cardiomyopathy. (3rd October 2022) - Gonzalez-Ferrero, T; Minguito-Carazo, C; Bergonti, M; Lopez-Canoa, J N; Garcia-Rodeja Arias, F; Otero-Garcia, O; Gonzalez-Maestro, A; Martinez-Sande, J L; Gonzalez-Melchor, L; Garcia-Seara, J; Fernandez-Lopez, J A; Gonzalez-Juanatey, J R; et al.
Abstract: Background: Atrial fibrillation (AF) is known to trigger a reversible dilated cardiomyopathy referred as arrhythmia-induced CM (AiCM). However, it remains unclear why some patients are more prone to develop AiCM than others and there is scarce information about their clinical outcomes after AF ablation. Purpose: We ought to find clinical and analytical predictors for the development of AiCM and recovery of LVEF in patients referred for AF ablation. Methods: A prospective multicenter study of consecutive patients undergoing point-by-point radiofrequency (RF) catheter ablation between September 2016 and November 2021 was conducted. The low voltage areas and left atrial (LA) volume were analyzed offline on high density electroanatomical maps collected prior to RF ablation. Peripheral blood sample for biomarker analysis (Gal-3, FABP4 and sRAGE) were obtained at the time of the procedure. Results: 803 consecutive patients were included, median age was 61 and 240 (30, 81%) were women. AF pattern was paroxysmal in 254 (32, 60%) and persistent in 534 (68, 55%; of whom, long-standing persistent in 113 (14, 51%) patients). The median follow-up period was 23.83 months [IQR 9 to 36]. The multivariate analysis revealed LA area, width of QRS segment, persistent AF and chronic kidney disease (CKD) as independent predictors for AiCM. Recurrence-free survival was not different amog both cohorts (Figure 1). The median increase in LVEF from baseline to the 6-month follow-up visit in patients with AiCM was 16% (CI 14.31–18.47) without changes in the non-AiCM group. The median LVEF previously to CA from patients in the AiCM group was 38% (IQR 30–45%) and after the procedure 57% (IQR 50–60%) [see figure 2]. Conclusions: AiCM is characterized to have a particularly complex pathophysiology not fully understood thus far. Pulmonary vein isolation in patients is safe and suitable for patients that suffered from tachycardiomyopathy. We found that persistent AF and chronic kidney disease play a key role in its development. Neither peripheral blood biomarkers nor left atrial samples showed relevant association with its occurrence. Funding Acknowledgement: Type of funding sources: None.